Inoculum dynamics of Ralstonia spp.: potential sources, persistence in a local population and selection of phages to reduce bacteria survival - Yamada, Jaqueline Kiyomi (2018)
Ralstonia spp. are known to cause bacterial wilt in several plants of economic interest. The pathogen has high genetic variability, wide host range and can survive in the soil even in the absence of hosts. Understanding potential inoculum sources that contribute to genetic variability in the center of origin is interesting to the management of the disease. The importance of rivers, weeds and native population of Ralstonia spp. in areas of natural vegetation in the development of epidemics of bacterial wilt is poorly understood. Genetic variability among strains of Ralstonia spp. in a local region where the disease is endemic can elucidate the contribution of the means of dispersal and factors of survival. In the present study, the detection of Ralstonia spp. was attempted in water of rivers of different biomes of Brazil and revealed the potential of these natural resources to disperse the pathogen. Weeds were important reservoirs of both species of Ralstonia that occur in Brazil, and collaborate to their survival. Methods of detection were not sensitive to confirm the presence of Ralstonia spp. in soil samples from areas without the occurrence of bacterial wilt. The genetic variability of 204 strains of R. solanacearum and 60 strains of R. pseudosolanacearum from the municipality of Coimbra, Minas Gerais, was low and there was evidence of clonality in the population. The population was not genetically structured according to the geographic region in the municipality, however the genotypic composition varied in time. To assess an alternative measure to control bacterial wilt, five phages were isolated. All phages belong to the Siphoviridae family, Caudovirales order. Molecular analysis and host range with different R. solanacearum strains revealed differences among the viruses. There were differences in the host range when the five phages were exposed to 24 Ralstonia spp. strains. The phages were not able to prevent tomato infection and control the number of cells of Ralstonia spp. in the soil. Other methods of application are necessary to evaluate the efficiency of the phages to control of bacterial wilt.